2014
DOI: 10.1016/s2215-0366(14)00006-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preoperative pain and depressive symptoms on the risk of postoperative delirium: a prospective cohort study

Abstract: Background Preoperative pain and depression predispose patients to delirium. Our goal was to determine whether pain and depressive symptoms interact to increase delirium risk. Methods We enrolled 459 persons without dementia aged ≥70 years scheduled for elective orthopedic surgery. At baseline, participants reported their worst and average pain within seven days and current pain on a 0–10 scale. Depressive symptoms were assessed using the 15-item Geriatric Depression Scale and chart. Delirium was assessed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 29 publications
1
47
1
2
Order By: Relevance
“…This may be due to the fact that age in our inclusion criteria (aged ≥ 70) was relatively high and the variation of age was relatively small. Previous studies have also documented that pain or inadequate pain control is likely to increase the risk of delirium [49], whereas our study showed that the degree of pain and the following opioid medication were not associated with the occurrence of postoperative delirium.…”
Section: Discussioncontrasting
confidence: 78%
“…This may be due to the fact that age in our inclusion criteria (aged ≥ 70) was relatively high and the variation of age was relatively small. Previous studies have also documented that pain or inadequate pain control is likely to increase the risk of delirium [49], whereas our study showed that the degree of pain and the following opioid medication were not associated with the occurrence of postoperative delirium.…”
Section: Discussioncontrasting
confidence: 78%
“…However, this decrease is small and, therefore, unlikely to have clinical signifi cance. Nevertheless, pain itself is a risk factor for the development of delirium, 38 so a delirium-spari ng pharmacoprophylaxis would seem to be a better strategy than increasing putative delirium-enhancing analgesic drugs to combat postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…Other clinically important factors identified in prospective studies were depression [28,29], preoperative pain [29], and the complex of sleep disordered breathing, including, among others, snoring, obstructive sleep apnea syndrome, and the upper airway resistance syndrome [30]. ApoE4, a marker of Alzheimer's disease, was no risk factor in surgical patients [31,32].…”
Section: Psychomotoric Subtypes Of Deliriummentioning
confidence: 99%